Ideology in Pramoedya Ananta Toer’s Footsteps - Gisa Vadhika Sacawisatra (Universitas Pendidikan Indonesia (UPI), 2016)
This study is conducted to construct ideology in Pramoedya Ananta Toer’s Footsteps. In order to construct ideology in the novel, Eagleton’s theory of six ideological features is employed as the tool to analyze the text. This study finds that there are two dominant class ideologies which are constructed in the novel, which are capitalism and feudalism. This study also finds that the characters are attributed with five ideological features, which are legitimation, rationalization, action-oriented, universalization, and naturalization to maintain the domination and advantages of the dominant classes and their ideologies.Keywords: ideology, unifying, action-oriented, rationalization, legitimation, naturalization, universalization